Quantification of swimmers` ability to apply force in the water: the potential role of two new variables during tethered swimming - Ruiz-Navarro, J. J.; Andersen, J. T.; Cuenca-Fernández, F.; López-Contreras, G.; Morouço, P. G.; Arellano, R. (Sports Biomechanics, 2022)
This study aimed 1) to examine variables that may quantify the ability to apply force in the water and 2) to test their relationship with free swimming performance. Sixteen regional-level swimmers participated in this study. Average (Favg) and maximum (Fmax) forces were measured for 30 s arm stroke tethered swimming in a flume at zero and 1.389 m/s water flow speeds. The maximum and average force`s relative changes (DeltaFmax and DeltaFavg, respectively) were calculated between tethered swimming at zero and 1.389 m/s water flow speeds. Free swimming speeds were obtained from 25, 50, and 100 m front crawl trials, and were correlated with DeltaFmax and DeltaFavg. A negative correlation was found between DeltaFmax and 25, 50 and 100 m speeds (r = -0.84, r = -0.74, r = -0.55; p < 0.05, respectively) and DeltaFavg correlated negatively with 25 and 50 m speeds (r = -0.63, r = -0.54; p < 0.05, respectively), but it did not correlate with 100 m swimming speed. The relative change in force could be used to quantify the ability to apply force in the water. This could aid coaches to understand if changes in swimmers` ability to apply force in the water contribute to improvements in performance.